An InterPlanetary File System (IPFS) based IoT framework - Shapna Muralidharan; Ko, Heedong (2019 IEEE INTERNATIONAL CONFERENCE ON CONSUMER ELECTRONICS (ICCE), 2019)
The Internet of Things (IoT) promises to bring immense value to various sectors by increasing efficiency and creating better experiences for the user. Currently, IoT works in a centralized, client-server model where data generated is stored and managed in centralized cloud servers. A concept of decentralized, peer-to-peer computing can ensure reliability, privacy, and interoperability in data management among IoT applications. The InterPlanetary File System (IPFS) is a peer-to-peer versioncontrolled file system which can envision a decentralized IoT system. In this paper, we have demonstrated the feasibility and advantage of IoT framework in a P2P decentralized storage infrastructure using IPFS through experimental evaluation using Raspberry Pi’s.
Keywords: IoT; Decentralized; IPFS